Protocol for an observational study to assess the impact of pharmacogenetics on outcomes in vascular surgery (PROSPER) - John H McDermott; William G Newman; Stuart Wright; Kerry Anne Burke; Selman Mirza; Nicholas S Greaves (BMJ Open)
Introduction Patients with chronic limb-threatening ischaemia (CLTI) are often prescribed clopidogrel in order to reduce their risk of major adverse limb and cardiovascular events. Clopidogrel is metabolised by the CYP2C19 enzyme and genetic variations in CYP2C19 are common. These variants can influence an individual’s ability to metabolise clopidogrel to its active metabolite. Few studies have investigated the relationship between patient genotype and outcomes in vascular surgery. This work aims to establish the relationship between patient genotype and outcomes after revascularisation in patients with CLTI who are prescribed clopidogrel. It will consider whether pharmacogenetics can be used to ensure patients are prescribed effective medications to optimise their outcomes.Methods and analysis This is an observational cohort study of patients undergoing lower limb surgical, endovascular or hybrid revascularisation for CLTI at Manchester University NHS Foundation Trust. Patients taking clopidogrel post-procedure, as well as those prescribed a non-clopidogrel based medication regimen, will be recruited prior to or shortly after revascularisation. Patients will undergo CYP2C19 genotyping and will be followed up using online records. The study has 90% power to detect 114 amputations with a target sample size of 483 participants. The primary outcomes are risk of amputation at 1 year and a composite endpoint for the risk of major adverse limb events (MALE) or death from any cause at 1 year. Secondary outcomes are risk of MALE at 1 year, risk of major adverse cardiovascular events (MACE) or death from any cause at 1 year, death within 30 days of revascularisation, minor re-interventions at 1 year, total number of re-interventions at 1 year and rate of systemic or gastrointestinal bleed at 1 year.Risk of amputation, MALE and MACE will be analysed using Cox models. All remaining outcomes will be analysed using negative binomial models. Potential competing events for the risk of amputation will be investigated as part of a sensitivity analysis. Patients given a non-clopidogrel-based medication will be compared as an additional analysis.Ethics and dissemination Manchester University Research Ethics Committee approval obtained as part of the Implementing Pharmacogenetics to Improve Prescribing (IPTIP) trial process (IRAS 305751). The results of the study will be published in a peer-reviewed journal and presented at international conferences.Registration This work is a sub-protocol for the IPTIP study which is registered as ISRCTN14050335.